Building Web-Based Job Management System Using the Laravel 8.0 Framework (Case Study: Muhammadiyah Lamongan Hospital) - D Efita Ningsi Husen; Danur Wijayanto (SENATIK STT Adisutjipto, 2022)
The Job Management System is a system that can make easier for Directors to monitor their completing tasks/projects employees. The application of Job Management at the SIRS Unit of the Muhammadiyah Lamongan Hospital is still done manually. Actually this is not a big thing, but it can affect the efficiency and effectiveness of employees in terms of collecting tasks/projects assigned by the project leader. In addition, the director as the highest leader at Muhammadiyah Lamongan Hospital also has to wait for a report from the project chairman to be able to get the final results of the project that is being worked on. For this reason, a web-based work management system was created using the waterfall method, Laravel 8.0 Framework, and MySQL database. The purpose of this system is to help the Director to be able to monitor the progress of a project carried out by employees in each unit. In addition, this system can assist the project leader in monitoring the progress of the project given by the Director. And the benefits that employees get are that they don't have to wait for offline meetings or regular meetings to collect tasks that have been done. This system also supports project team members to improve effectiveness, time efficiency, and quality of work.